Risk attitudes, job mobility and subsequent wage growth during the early career - Michael Maier; Bethlehem A. Argaw; Michael F. Maier; Olga J. Skriabikova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we investigate the relationship between individuals' willingness to take risk and job mobility during the early career. Job change is a risky decision since it involves substantial costs without entirely foreseeing the benefits at the time the decision is made. We incorporate risk preferences as an additional parameter influencing the individual job change behaviour in an on-the-job search model accounting for nonwage job characteristics. Empirically, we show that more risk-averse individuals voluntarily change their jobs less often compared to more risk-tolerant individuals. In addition, since risk-averse individuals demand higher compensation for the risk associated with uncertain nonwage job characteristics, we find that their job changes are associated with higher wage gains. However, more risk-averse individuals do not obtain higher overall wage growth as a result of the early career compared to more risk-tolerant individuals.
Keywords: D81; J31; J62; 330